Sistem Among Ki Hajar Dewantara dan Relevansinya dengan Pendidikan Islam - Lilik Fajar Anshor; Rustam Ibrahim (Journal on Education, 2024)
Education is a fundamental aspect in character building and the progress of a nation. In Indonesia, discourse on education cannot be separated from the thoughts of Ki Hajar Dewantara, who is known as the Father of National Education. One of his greatest contributions is the Among System, an educational approach that emphasizes freedom, independence, and humanistic guidance. Ki Hajar Dewantara's Among System was born as a response to the colonial education system that tended to ignore the cultural values ​​and character of the Indonesian nation. This Among System, by Ki Hajar Dewantara, is associated with character education carried out with the principles of asih, asah, and asuh. Furthermore, this system is related to the motto Ing Ngarso Sung Tulodho, Ing Madya Mangun Karsa, Tut Wuri Handayani. On the other hand, Islamic education has become an integral part of the Indonesian national education system. In this context, it is interesting to examine how Ki Hajar Dewantara's Among System can synergize with the principles of Islamic education. The relevance between the Among System and Islamic education is important to study considering that both have similar goals, namely to form humans who are noble, independent, and useful to society. Integration of local wisdom values, as contained in the Among System, with Islamic education can produce a more contextual and effective education model in shaping students' characters. Based on this background, this paper will examine the Ki Hajar Dewantara Among System and its relevance to Islamic education. This study is expected to contribute to the development of an integrative education system, which combines local wisdom, Islamic values, and the demands of modern education in Indonesia.